Assessing the Quality of Voice using E-Model for Optimized Congestion Control approach in Mobile Ad-hoc Network - Savithri, V; Marimuthu, A (International Journal of Computer Sciences and Engineering, 2025)
Congestion is an unsolvable and challenging issue for real time data such as voice especially in MANET. Since mobile devices support limited bandwidth, limited battery power, dynamic links and frequently changing routing decision, controlling congestion is a challenging and critical task. Also voice transmission requires valid data to be delivered at receiver by supporting less End-End-Delay. Hence there exists a need to apply dynamic and efficient routing schemes which handle congestion and reduce its severity, proactively avoid congestion before its occurrence. The state of storing packet continuously causes router queue to overflow and drops the incoming packet. Packet drop at these router queues also forecasts nearing congestion. Hence router queue uses various queue management approaches to minimize the occurrence of packet drop and congestion. RED based flavors of proactive queue management schemes received a lot of attention in recent years in controlling congestion over MANET. In this paper, we propose a congestion control approach that supports three different interdisciplinary approaches to control congestion on voice data transmission. Finally we evaluate the performance of the proposed approach using E-Model and compare the performance of the three approaches in order to identify the best approach that supports improved quality at user level. Fuzzy logic based congestion control approach shows improved performance